Preparation and Characterization of Microencapsulated Ammonium Polyphosphate with Polyurethane Shell and Its Flame Retardance in Polypropylene - Thuy Tien Nguyen Thanh; Ziya Yusifov; Bence Tóth; Katalin Bocz; Péter Márton; Zoltán Hórvölgyi; György Marosi; Beáta Szolnoki (Fire, 2024)
Polypropylene (PP) shows no charring ability in burning due to the lack of hydroxyl functional groups; thus, the flame retardant system needs an additional amount of carbonizing agent. An ammonium polyphosphate (APP)-based all-in-one intumescent flame-retardant system was prepared by the in situ polymerization of polymeric methylene diphenyl diisocyanate (pMDI) with a glycerol-based and a glycerol–sorbitol-based polyol of high OH value. The microencapsulated APP with a polyurethane shell (MCAPP) of different polyols was characterized. The MCAPP with speculated improved flame retardant performance was selected for further evaluation in the PP matrix at different loadings by means of standard flammability tests.